The Twilight and Eclipse of Literature in the School of Paper: Manufactured Tensions and Newartisanal Nuances (Global Journal of Human-Social Science, 2023)
The reading and teaching of literature is a central theme of various fields of study such as Applied Linguistics which has investigated it in contexts of uses of language practices such as the public school classroom The aim of this article is to investigate the teaching of literature in elementary and high school in artisanal manufacturing dualistic unique paper and neoartisanal schools based on the metaphors twilight eclipse and dawn discussing tensions disturbances and nuances that these phenomena provoke in educational actors and in the public institution itself This work is based on theoretical and methodological bases of literary education the schooling of the literary text and paradigms of literature teaching With a qualitative approach of a basic nature the phenomena in these institutions are investigated through the bias of bibliographical research
Keywords: paper schools neoartesanal school paradigms of literature teaching reader education and literary literacy